Review on the synthesis of LiNixMnyCo1-x-yO2 (NMC) cathodes for lithium-ion batteries. (August 2022) - Malik, Monu; Chan, Ka Ho; Azimi, Gisele
Abstract: The second-generation lithium-ion batteries (LIBs) using the layered LiNix Mny Co1-x-y O2 cathode material have a wide range of applications from electronics to electric vehicles due to their high volumetric and gravimetric capacity, high nominal voltage, and low self-discharge. Considering the performance of LIBs depends on the composition, crystallography, morphology, and other parameters during synthesis, interest in developing high-performance LIBs has motivated researchers to develop novel synthesis methods to precisely control these parameters. Significant progress has been made in the advancement of several synthesis methods such as coprecipitation, sol-gel, hydrothermal, and solid-state. Moreover, new methods such as Pechini, combustion, emulsion-drying, and RAPET method have been successfully utilized to synthesize LiNix Mny Co1-x-y O2 . Motivated by this rapid advancement, this review paper presents all synthesis methods used for the production of crystalline LiNix Mny Co1-x-y O2 for LIBs and discusses the effect of various synthesis parameters on the properties of the cathode material and battery performance. The research summaries in this work are targeted to provide researchers in the battery industry with a pathway for deciding the synthesis conditions for LiNix Mny Co1-x-y O2 production. This work highlights the challenges associated with each synthesis method and motivates researchers to further investigate and enhance these methods to achieve the highest performance of LiNix Mny Co1-x-y O2 . Graphical abstract: Image 1 Highlights: Methods for synthesizing NMC cathodes significantly impact battery performance. Coprecipitation and spray pyrolysis are best suited for industrial applications. Detailed investigation of new synthesis methods is required for industry application. Industry shift toward Ni-rich cathode and advanced synthesis methods are needed.